Effect of ratio of Pineapple Pulp with Carrot Pulp and Stabilizer Type on the Quality of Jam Sheet - Theresia Hutagalung; Rona J. Nainggolan; Mimi Nurminah (Universitas Sumatera Utara, 2016)
The aim of this research was to find the effect of ratio of pineapple pulp with carrot pulp and stabilizer type on the quality of mixture of pineapple and carrot jam sheet. The research was conducted by using completely randomized design with two factors, i.e. : ratio of pineapple pulp and carrot pulp (B) : (85% : 15% ; 75% : 25% ; 65% : 35% ; 55% : 45%) and stabilizer type (P) : (CMC, Carrageenan, Arabic gum, Pectin). Parameters analyzed were moisture content, vitamin C content, total soluble solid, total acid, crude fiber content, organoleptic score values of color and texture and organoleptic hedonic values of taste and flavor. The results showed that the ratio of pineapple pulp with carrot pulp had highly significant effect on moisture content, vitamin C content, total soluble solid, total acid, crude fiber content, organoleptic score values of color and texture and organoleptic hedonic values of taste and flavor. Stabilizer type had highly significant effect on moisture content, vitamin C content, total soluble solid, total acid, crude fiber content, organoleptic score values of color and texture, organoleptic hedonic values of taste and flavor. Interaction of the two factors had highly significant effect on organoleptic score values of texture and had no effect on moisture content, vitamin C content, total soluble solid, total acid, crude fiber content, scores values of color, hedonic values of flavor and taste. The ratio of pineapple pulp with carrot pulp of (85% : 15%) and CMC produced the best quality more acceptable jam sheet. Keywords : Carrot, Jam sheet, Pineapple, Stabilizer type.